Industrial Inorganic Chemistry - Benvenuto, Mark Anthony (De Gruyter Textbook, 2024)
Industrial Inorganic Chemistry adds to the previously published graduate level textbooks on Industrial Chemistry by Mark A. Benvenuto. It focuses specifically on inorganic processes, from the largest industrial process for the production of major inorganic chemicals and metals, down to and including smaller niche processes that have become extremely important in maintaining the current quality of life. The book provides a survey on the production of essential elements and compounds, such as sulfuric acid, calcium carbonate, fertilizers as well as numerous metals and alloys. In addition to the fundamental scientific principles each chapter includes discussions on the environmental impacts: mining of raw materials, creation of by-products, pollution, and waste generation, all of which have become key factors for the potential implementation of greener methods. The author also highlights ways in which industry has begun to make industrial inorganic processes more environmentally benign. Examines major inorganic chemistry processes, their effect on every-day life and current efforts to improve processes or adapt "green" chemical production. Provides didactic links between theoretical lecture contents and current, largescale chemical processes. Valuable for students of Inorganic Chemistry, Industrial Chemistry, Chemical Engineering and Materials Science.